Limits on the nuclearite flux using the ANTARES neutrino telescope. Issue 1 (1st January 2023) - Albert, A.; Alves, S.; André, M.; Ardid, M.; Ardid, S.; Aubert, J.-J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; Benfenati, F.; et al.
Abstract: In this work, a search for nuclearites of strange quark matter by using nine years of ANTARES data taken in the period 2009–2017 is presented. The passage through matter of these particles is simulated taking into account a detailed description of the detector response to nuclearites and of the data acquisition conditions. A down-going flux of cosmic nuclearites with Galactic velocities ( β = 10 -3 ) was considered for this study. The mass threshold for detecting these particles at the detector level is 4 × 10 13 GeV/ c 2 . Upper limits on the nuclearite flux for masses up to 10 17 GeV/ c 2 at the level of ∼ 5 × 10 -17 cm -2 s -1 sr -1 are obtained. These are the first upper limits on nuclearites established with a neutrino telescope and the most stringent ever set for Galactic velocities.